Development of molecularly imprinted polymers specific for blood antigens for application in antibody-free blood typing. Issue 11 (14th December 2016) - Piletsky, S. S.; Rabinowicz, S.; Yang, Z.; Zagar, C.; Piletska, E. V.; Guerreiro, A.; Piletsky, S. A.
Abstract : A novel system for blood type testing is developed based on the first molecularly imprinted nanoparticles specific to oligosaccharides. Abstract : A novel approach in antibody-free blood typing based on molecularly imprinted polymeric nanoparticles is described.